(untitled) (Journal of humanities and social sciences exploratio, 2025)
With the rapid development of digital technology, red publications are encountering new opportunities and challenges in terms of dissemination. This study focuses on optimizing the interaction design and constructing copyright protection mechanisms for red publications in a digital environment, aiming to enhance their influence and dissemination effectiveness among young people while preventing potential copyright risks associated with digital distribution. By analyzing the current state of red publications in terms of content presentation, user experience, and copyright management, and integrating digital media theory and related copyright protection systems, a dual approach combining interaction design and technical safeguards is proposed. In terms of interaction design, the focus is on a user-centered approach, improving content readability, interactivity, and emotional resonance; for copyright protection, the feasibility of technologies such as blockchain and digital watermarking in preventing illegal distribution and tampering is examined. Practice has shown that reasonable interaction design can effectively increase user engagement, and multilayered copyright protection benefits the legitimate rights and interests of content creators. The research outcomes provide theoretical support and practical reference for the digital transformation and sustainable dissemination of red cultural resources, and in the future, technologies such as artificial intelligence can further expand the possibilities of red publications in smart reading and cross-platform distribution.